Upacara Karya Lilitan sebagai Ritual Sakral dalam Struktur Kehidupan Catur di Desa Adat Dalem Tamblingan - Trisiana, Irvan; Suastika, I Nengah; Budiarta, I Wayan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
The Karya Lilitan Ceremony is a sacred ritual that plays a central role in the spiritual, social, and ecological life of the Catur community of Dalem Tamblingan Traditional Village, Bali. This ritual is not merely a religious practice, but also functions as a cultural mechanism for preserving local values, strengthening social cohesion, and maintaining cosmic balance between humans, nature, and ancestral spirits, as reflected in the philosophy of Tri Hita Karana. This study aims to describe the meaning, stages, and socio-ecological functions of the Karya Lilitan Ceremony within the customary institutional structure of the community, with particular attention to the role of the Gama Tirta Charter, which venerates water as a source of life and a sacred spiritual medium. The research employed a qualitative descriptive approach through literature review, participatory observation, and semi-structured interviews with traditional leaders, temple custodians, and customary institution representatives. The findings indicate that the Karya Lilitan Ceremony serves as an effective cultural mechanism for maintaining collective identity, strengthening intergenerational social solidarity, and enhancing ecological awareness among indigenous communities. The active involvement of all community members throughout the extended ritual process demonstrates a strong integration of spirituality, customary governance, and environmental conservation based on local wisdom. Thus, the Karya Lilitan Ceremony represents not only a form of religious heritage but also a sustainable socio-ecological model rooted in indigenous cultural traditions. Keywords: Karya Lilitan Ceremony, Catur of Dalem Tamblingan Traditional Village, Sacred Rituals, Gama Tirta Charter, Cosmic Balance